Implementation of Population Control and Family Planning Policy at the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning of Banda Aceh City - Dini, Dini Ramadini; Aisyah, Siti; Hafni, Nur; Ilham, Ridha (JOELS: Journal of Election and Leadership, 2025)
Abstract The purpose of this study is to examine how the Population Control and Family Planning Policy is implemented by the Office of Women Empowerment, Child Protection, Population Control, and Family Planning in Banda Aceh City. The research applies a qualitative descriptive method through interviews, observations, and document analysis. The findings show both supporting and inhibiting factors in policy implementation, including resources, communication, and organizational structure.The research focuses on three main questions: how the policy is implemented, what supporting and inhibiting factors exist, and what strategies can be applied to improve its implementation. A qualitative approach was employed, with data collected through in-depth interviews using an interview guide. Informants included institutional leaders, family planning field officers, and other relevant stakeholders. Data were analyzed by categorizing responses, classifying findings, and reviewing interview transcripts and audio recordings based on source and date. The findings reveal that policy implementation is influenced by four key aspects: communication, which ensures clarity of program delivery, methods, objectives, and target groups; resources, including adequate personnel, facilities, and infrastructure; disposition or attitude, reflected in motivation, commitment, and the use of rewards and punishments; and organizational structure, supported by technical guidelines, regulations, and implementation manuals. Supporting factors include sufficient facilities, competent human resources, and clear regulations, while constraints are primarily limited budgets and the lack of competence among some implementers. Strategies to strengthen policy implementation involve continuous socialization, expanding outreach to various partners, and collaborative approaches with religious, traditional, and community leaders. This study highlights the importance of synergy between communication, resources, attitudes, and organizational structures in ensuring the success of population control and family planning programs in Banda Aceh City.